Analysis of Competitiveness and the Impact of Government Policy on Patchoulicommodity in Pasaman Barat District - Muhammad Farrasky Delas Putra; Faidil Tanjung; Ifdal (Enrichment : Journal of Management, 2021)
Patchouli oil is Indonesia's potential essential oil which is widely traded in the world market. This study aims to analyze the competitiveness of patchouli commodities in West Pasaman Regency and analyze the impact of government policies on the competitiveness of patchouli commodities in West Pasaman Regency. The method used in this research is a survey method. Analysis of the data used in this research is descriptive quantitative using a measuring instrument Policy Analysis Matrix (PAM). The results showed that Patchouli Farming in West Pasaman Regency already has competitiveness based on the acquisition of private and social benefits as well as competitive advantages and comparative advantages. Competitive advantage is expressed by a PCR value of 0.64 < 1. Comparative advantage is reflected by a DRC value of 0.56 < 1. PCR and DRC values that are smaller than one indicate that the commodity has competitiveness. The closer the value is to 0, the commodity has high competitiveness and is very profitable to cultivate. The impact of government policies shows that there are government policies that inhibit commodities with taxes on output and there are government policies that are protective of tradable inputs. This is indicated by the value of the Nominal Protection Coefficient of Patchouli commodity output of 0.89; Nominal Protection Coefficient Input of 0.48; Effective Protection Coefficient of 0.90; Profitability Coefficient of 0.73; and the Subsidy Ratio to Produce of -0.12.